全方位水平姿态爬楼机器人机械系统研究 - 毛立民; 梁虎; 林绍碧; 陶程杰; 刘智韬 (Jixie chuandong)
An omnibearing level posture climbing robot is introduced,and it is a robot with three degrees of freedom.By using the three degrees of freedom,the robot can climb obstacle,stairs and turn zero radius turn movement,etc..By using schematic drawings,the theory of the robot,the walking theory,stair climbing theory of the robot are introduced,the rotation mechanism of the robot is analyzed,the relationship between rotational motion and displacement distance,the average distribution of displacement to keep the robot balance are deduced,and the FEA of the key parts is carried out.